Population Pharmacokinetic Analysis of Digoxin in Chinese Neonates and Infants - Yan Gong; Yewei Chen; Qin Li; Zhiping Li (Elsevier, 2014)
Abstract.: To obtain more information regarding the influence of various covariates on the disposition of digoxin in Chinese neonates and infants, routine clinical pharmacokinetic data were retrospectively collected from 131 hospitalized patients. A nonlinear mixed effects modeling (NONMEM) method was applied to the data. A one-compartment/first-order absorption model was employed to estimate the influence of total body weight (allometric power model), postnatal age, serum creatinine, gender, presence of heart congestive failure, and concomitant medications on apparent total clearance and apparent drug distribution of digoxin. Pharmacokinetic parameter estimates for CL/F and V/F were 0.147 L∙h−1∙kg−1 and 15.7 L/kg, respectively. Total body weight and postnatal age were identified as the important factors affecting total clearance of digoxin; total body weight was the covariate identified to influence the apparent distribution volume. Both internal (bootstrap method, visual predictive checks, and normalized prediction distributed error) and external validation supported the stable and predictive performance of the final model. We concluded that the model can be used to choose an appropriate dose regimen in Chinese neonates and infants. Keywords:: digoxin, neonate, nonlinear mixed effects modeling, allometric scaling, pharmacokinetics